Magnetic imaging of antiferromagnetic and superconducting phases in RbxFe2-ySe2 crystals - Speller, S; Mousavi, T (University of Oxford, 2018)
The data files are standard image files (.png and .eps versions) and numerical data files (.csv) for the graphs. These can be read with many different software packages.